A Sharia Risk Taxonomy for Multi-Akad Banking Contracts - Anik Anik; Yazid Afandi; Anom Garbo (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
challenges that may not be adequately identified by assessing each constituent contract separately. This study aims to develop a conceptual taxonomy of Sharia compliance risks arising from the interaction between contracts and to propose a structured framework for supervising multi-akad products in Indonesian Islamic banking. The study employs a qualitative normative approach through structured analysis of selected DSN-MUI fatwas, Indonesian banking regulations, Islamic economic law documents, and relevant academic literature. The analysis involves contract decomposition, identification of legal and operational interfaces, classification of potential exposure to riba, gharar, and maisir, and interpretation through maqāṣid al-Sharīʿah principles. Three selected contract configurations are examined: murabahah–ijarah, murabahah-wakalah, and musharakah mutanaqishah. The analysis suggests that compliance vulnerabilities may arise not only within individual contracts but also from their sequencing, ownership transfer, pricing mechanisms, disclosure requirements, and risk allocation. Based on these conceptual findings, the study proposes a Sharia Risk Taxonomy and an integrated Sharia Compliance and Risk Management framework comprising a maqāṣid-based evaluation grid, an interface risk protocol, a dual-competence Sharia Supervisory Board model, and a dynamic monitoring system. As a normative-conceptual study, the proposed framework has not been empirically validated and should therefore be tested through product-level case studies, expert assessment, and institutional implementation research.